1996
DOI: 10.1006/lich.1996.0005
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll A Fluorescence and Chlorophyll Content in Parmelia Quercina Thalli from a Polluted Region of Northern Castellon (Spain)

Abstract: Measurements of modulated chlorophyll a fluorescence emission and chlorophyll content were made in thalli of Parmelia quercina collected from northern Castellon(Spain). Althoug high air pollution concentrations have been measured in this area, the ratio of variable to maximal fluorescence is unaffected. Following dark-adaptation, the response to irradiance of chlorophyll fluorescence was examined. With respect to control samples, thalli collected in northern Castellon consistently showed differences in fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…Another study [26] reported on the effects of ozone fumigation and revealed a significant reduction of the variable fluorescence/maximal fluorescence (F v /F m ) ratio in five of the seven investigated macrolichens, thus indicating severe stress on photosystem II (PSII) due to ozone. A study of chlorophyll a fluorescence carried out in Spain detected a similar F v /F m for thalli in polluted regions and for control samples [27]. Another study on this subject carried out in Poland found significantly lowered fluorescence parameters in three lichen species from the more polluted site [28].…”
Section: Introductionmentioning
confidence: 81%
“…Another study [26] reported on the effects of ozone fumigation and revealed a significant reduction of the variable fluorescence/maximal fluorescence (F v /F m ) ratio in five of the seven investigated macrolichens, thus indicating severe stress on photosystem II (PSII) due to ozone. A study of chlorophyll a fluorescence carried out in Spain detected a similar F v /F m for thalli in polluted regions and for control samples [27]. Another study on this subject carried out in Poland found significantly lowered fluorescence parameters in three lichen species from the more polluted site [28].…”
Section: Introductionmentioning
confidence: 81%
“…An additional study of the impact of a chemical pollutant on Chl fluorescence in dark-adapted lichens revealed an impairment of PSII photochemical reactions, measured as a decrease in F v /F m as a result of Pb uptake, particularly in cyanobiont lichens (Branquinho et al 1997b). On the other hand, a study of Chl a fluorescence in lichen thalli, from a polluted region in Spain, revealed a F v /F m ratio that was about the same as for control samples (Calatayud et al 1996).…”
mentioning
confidence: 87%
“…There is a substantial body of evidence that NPQ may reflect the capacity of plants and lichens to carry out non‐radiative dissipation of excess energy ( Demmig‐Adams et al 1990). Previous work from our laboratory with the lichen P. quercina from polluted and control sites has shown that NPQ is affected by the presence of phytotoxic pollutants ( Calatayud et al 1996). Thus, environmental stresses might also affect heat emission and reduce the ability for safely dissipating absorbed energy.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling grounds fall within the area covered by a government air monitoring network, so that a continuous record on atmospheric pollutants is available since 1991. High O 3 concentrations have been recorded for long periods in the area as a result of complex photochemical processes ( Calatayud et al 1996). The experimental sites were selected after taking into account different variables, such as visible damage to surrounding vegetation and lichens, direction of prevailing winds and proximity to monitoring stations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation